U.S. vulnerability to an oil import curtailment : the oil replacement capability - United States (Washington, D.C. : Congress of the U.S., Office of Technology Assessment : For sale by the Supt. of Docs., U.S. G.P.O., 1984)
This report analyzes energy supply and demand technologies which can replace large amounts of oil within 5years after the onset of a major oil supply shortfall, occurring within the next few years and accompanied by a large and enduring increase in oil prices.
"September 1984"--P. [4] of cover.
"OTA-E-243"--P. [4] of cover.
S/N 052-003-00963-3
Item 1070-M
Includes bibliographical references and index.
hza 25/02/2019
Keywords: Petroleum industry and trade; Petroleum conservation; Petroleum reserves; Energy policy; National security